Extracellular Vesicles Derived from Mesenchymal Stromal Cells : A Multidisciplinary Analysis of Methodology, Efficacy and Biodistribution in Lung Disease - Tieu, Alvin (Université d'Ottawa / University of Ottawa, 2023)
Acute respiratory distress syndrome (ARDS) is a devastating critical illness that holds the highest cost of any acute care condition in Canada. In ARDS, a localized inflammatory response caused by lung infection or injury leads to vascular damage and migration of inflammatory cells into the airways resulting in impaired gas exchange and respiratory failure. Despite decades of research, there are no curative therapies for this daunting acute lung condition. Animal studies have demonstrated a potential for mesenchymal stromal cells (MSCs) to reduce inflammation, promote tissue regeneration and improve survival in acute lung injury (ALI, the preclinical correlate of ARDS). In particular, a growing body of evidence suggests that MSCs elicit their protective effects in large part by secretion of small membrane-bound particles known as "extracellular vesicles". These vesicles carry biologically active cargo that modulate critical cell processes including programmed cell death, proliferation and inflammation. Hence, MSC-derived extracellular vesicles (MSC-EVs) may have advantages as a safer off-the-shelf, cell-free immune modulatory therapy. However, the optimal approach for isolating and administering MSC-EVs have yet to be established within this new field of regenerative medicine. The aims of this project were to: (1) evaluate the current preclinical evidence on methodology and efficacy of MSC-EVs, (2) determine the effectiveness of MSC-EVs for ALI and other pulmonary diseases in animal models, and (3) explore the kinetics and biodistribution of MSC-EVs during healthy and disease state as a prerequisite to designing optimal therapeutic strategies. By combining both clinical meta-research methodology and basic science techniques, I hoped to create a comprehensive evidence map of mechanistic insights and the therapeutic benefits of MSC-EVs. Importantly, ARDS is recognized as the main cause of mortality for patients with COVID-19. In response to the SARS-CoV2 pandemic and restrictions placed on routine, non-COVID related lab work, an additional objective for my PhD focused on developing a novel, more accessible mouse model of COVD-19 associated ARDS. A SARS-CoV2 "pseudovirus" was created to enable its use in a less stringent Containment Level 2 lab setting. Dose-escalation experiments in mice helped determine the optimal dose that produces clinically-relevant COVID-19 ARDS pathology. Moreover, the specificity of our pseudovirus to human ACE2 receptors was tested using preclinical models. If successful, this model will allow researchers worldwide to study key mechanisms in COVID-19 pathophysiology and investigate novel vaccines or therapies to combat this global pandemic.
Keywords: Mesenchymal Stromal Cells; Mesenchymal Stem Cells; Extracellular Vesicles; Exosomes; Microvesicles; Acute Respiratory Distress Syndrome; Acute Lung Injury; COVID-19